IoT Based Electricity Energy Meter Using Arduino and Esp8266 - Archita, Archita; Mansi S. Kudalkar; Shweta S. Chougule; Pratiksha P. Kumbhar; C. P. Shinde (Advance Research in Communication Engineering and its Innovations, 2024)
As more people need electricity, many still use old meters. But with Wi-Fi at home, we can use IoT technology to track electricity use online. This system measures voltage, current, and power in real-time. Users can check their monthly electricity use on a user-friendly app or webpage. These pages can even connect to other power companies to automatically generate bills. Real-time values like kilowatt-hours are sent to an online database. Users can see this information on their app or webpage, helping them understand and reduce their electricity use. This device cuts down on manual meter readings and reduces billing errors. By upgrading to this system, households and businesses can better manage their electricity consumption and contribute to a more efficient and sustainable energy future. With the convenience of online monitoring and automated billing, the transition to modern electricity tracking becomes seamless. This innovative solution not only benefits individual consumers but also enhances the overall efficiency of electricity distribution networks. By embracing IoT technology, we can pave the way for smarter and more environmentally friendly energy usage practices.